2014
DOI: 10.3892/mmr.2014.3011
|View full text |Cite
|
Sign up to set email alerts
|

Proteasome inhibitor-induced autophagy in PC12 cells overexpressing A53T mutant α-synuclein

Abstract: The aim of the present study was to examine the effects of proteasome inhibitor (PI)-induced autophagy on PC12 cells overexpressing A53T mutant α-synuclein (α-syn) by detecting alterations in the levels of microtubule-associated protein 1A/1B light chain (LC3)+ autophagosomes and the lysotracker-positive autolysosomes using immunofluorescence, the expression of LC3-II using western blot analysis and the morphology of PC12 cells using transmission electron microscopy. It was found that the addition of MG132 (50… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
30
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 30 publications
5
30
0
Order By: Relevance
“…Consistent with other reports (Lan et al, 2015;Tang et al, 2014), analysis of the autophagosome marker LC3-II showed that proteasomal inhibition promoted enhancement of the autophagic flux. Silencing of LAMP3 impaired the induction of autophagic flux and promoted cell death.…”
Section: Discussionsupporting
confidence: 89%
“…Consistent with other reports (Lan et al, 2015;Tang et al, 2014), analysis of the autophagosome marker LC3-II showed that proteasomal inhibition promoted enhancement of the autophagic flux. Silencing of LAMP3 impaired the induction of autophagic flux and promoted cell death.…”
Section: Discussionsupporting
confidence: 89%
“…As previously reported [77,36,78], inhibition of the proteasome with MG132 induces autophagy (Suppl. Fig.…”
Section: Resultssupporting
confidence: 72%
“…According to previous reports, the pathological changes in α-synuclein, such as its overexpression and formation of oligomers, inhibit autophagy (39, 40). As shown in this work, iron deposition led to dysfunctional autophagy and α-synuclein pathology.…”
Section: Resultsmentioning
confidence: 91%